Varieties of Veterans’ Courts: A Statewide Assessment of Veterans’ Treatment Court Components - Douds, Anne S. (Criminal justice policy review, 2017)
Since the mid-2000s, there has been an upsurge in the development of Veterans’ Treatment Courts (VTCs) to support justice-involved veterans’ treatment needs while also providing criminal justice supervision. Despite their prolific development in recent years, there is a dearth of scholarly research on how VTCs are structured and whether there are common components across courts. There is a need to understand how VTCs are structured and operationally implemented to inform additional program planning and evaluation. To bridge this gap in the literature, this study provides a statewide assessment of the 17 VTCs operating in Pennsylvania, identifies six common components, and highlights areas in which their implementation diverges between courts to meet the specific needs of veterans across Pennsylvania. The results of this study provide a baseline framework to aid future researchers in conducting process and outcome evaluations by documenting and examining the common components of VTCs.